Comparison of Apical Leakage Patterns Shown by Two Different Methods - Jalil MODARESI; Abdorahim DAVARI; Alireza DANESHKAZEMI (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2007)
Purpose: To compare the apical leakage using dye penetration and electrochemical methods each successively used on the same teeth.Methods: 31 freshly extracted anterior single root human teeth with straight root canals were selected. The specimens were divided randomly, respectively into experimental group, two positive and two negative controls. Root canal of the case group and negative group were filled, and positive group were left unfilled. The external surface of each tooth was coated with two layers of the nail polisher, except for the apical 2mm and coronal portion. Leakage of each tooth was measured by using electrochemical test. Two copper wires were used as electrodes and normal saline solution was used as electrolyte. Then coronal portion of root were filled with the aid of ZOE cement and coated with two layers of the nail polisher. The teeth immersed in 2% basic fuchsine for 48 hours and were washed in tap water. The roots were then split longitudinally and dye leakage was assessed for each tooth.Results: No correlation was found among the results obtained with the two methods (P-Value=.297).Conclusions: Several studies are necessary before evaluation of the marginal leakage.